The problem of extension for two-parameter kernels - Lavrent'ev, A. S.; Mishura, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We solve the problem of construction of a two-parame to either a multiplicative or a coordinatewise two-parameter semigroup. The construction is carried out on the basis of the “initial family of kernels.”